2009
DOI: 10.1158/0008-5472.sabcs-09-76
|View full text |Cite
|
Sign up to set email alerts
|

Central Review of ER, PgR and HER2 in BIG 1-98 Evaluating Letrozole vs. Letrozole Followed by Tamoxifen vs. Tamoxifen Followed by Letrozole as Adjuvant Endocrine Therapy for Postmenopausal Women with Hormone Receptor-Positive Breast Cancer.

Abstract: Background: The BIG 1-98 trial, a large international Phase III study, evaluated letrozole (Let) for 5 years (n=1546) vs. Let for 2 years followed by tamoxifen (Tam) for 3 years (L→T; n=1540) and vs. Tam for 2 years followed by Let for 3 years (T→L; n=1548) as initial adjuvant endocrine therapy for postmenopausal women with hormone receptor-positive breast cancer. Patients with HER2-positive disease did not receive trastuzumab. Efficacy results were presented in SABCS 2008 and showed that neither of the sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
1
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 0 publications
2
20
1
1
Order By: Relevance
“…In particular lymph node status was prognostic but not predictive of chemotherapy response. This confirms findings by other studies that the genomic markers cannot replace but rather compliment prognostic information derived from anatomical pathological variables [3,6,[14][15][16]. Also, even though all of the genomic predictors had statistically similar performance and in multivariate analysis they provided no independent information, when applied to individual patients they frequently yielded discordant risk prediction results.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In particular lymph node status was prognostic but not predictive of chemotherapy response. This confirms findings by other studies that the genomic markers cannot replace but rather compliment prognostic information derived from anatomical pathological variables [3,6,[14][15][16]. Also, even though all of the genomic predictors had statistically similar performance and in multivariate analysis they provided no independent information, when applied to individual patients they frequently yielded discordant risk prediction results.…”
Section: Discussionsupporting
confidence: 87%
“…In almost all studies, these anatomical pathological variables remain statistically significant independent predictors of prognosis (i.e., probability of survival in the absence of systemic adjuvant therapy) [3,6,[14][15][16]. However, neither tumor size nor nodal status has a strong and consistent association with treatment sensitivity (i.e., probability and extent of response to therapy).…”
mentioning
confidence: 99%
“…Central subset analyses of tumor blocks of patients enrolled in the ATAC and BIG 1-98 trials 23,24 demonstrated that AIs were superior to tamoxifen irrespective of the degree of positivity of ER, HER-2 status, and progesterone receptor (PgR) status. In the neoadjuvant literature, Ellis et al reported that letrozole was superior to tamoxifen at all levels of ER expression between Allred scores of 3 and 8.…”
Section: Discussionmentioning
confidence: 99%
“…As HER2/neu overexpression and amplification are highly correlated with estrogen-receptor positive/progesterone-receptor negative status [71], these results may reflect an interaction between HER2/neu status and anastrozole therapy. However, an abstract from the BIG 1-98 trial [72] reported no obvious difference between estrogenreceptor positive/progesterone-receptor positive (hazard ratio 0.84, 95% confidence interval 0.69 to 1.03) and the estrogen-receptor positive/progesterone-receptor negative (hazard ratio 0.83, 95% confidence interval 0.62 to 1.10) subgroups comparing letrozole versus tamoxifen, so this relationship may not hold across all aromatase inhibitors. If and when HER2/neu subgroup analyses are published from these trials, it may then be possible to make a definitive statement regarding aromatase inhibitor therapy and HER2/neu status.…”
Section: Discussionmentioning
confidence: 99%